Social transformation and the transition from vocational education to work in Hungary : a differences-in-differences approach - Noelke, Clemens [Verfasser]; Horn, Dániel [Verfasser] (My University, 2014)
"The 'dual system' combining school-based vocational education with employer-provided training is often praised for effectively integrating young people into the labour market and recommended as a model for countries struggling with high youth unemployment. However, without an institutional framework supporting employer involvement, it has proven difficult to elicit or maintain what is essentially voluntary provision of training places by employers. Whenever employers are unwilling to train, school-provided training represents a viable alternative, but to date we know little about the relative effectiveness of school- vs. employer-provided training. This study exploits a rapid shift of training provision from employers to vocational schools that occurred during the Hungarian transformation from socialism to capitalism to analyse how these different ways of organizing training affect the labour market entry of vocational graduates. Our expectation is that the substitution of employer- with school-provided training has resulted in higher unemployment and lower job quality, particularly on leaving school. Results from differences-in-differences analyses indicate that the shift in training provision from employers to schools between 1994 and 2000 has increased male vocational school graduates' unemployment rate by 10 percentage points within the first 2 years after graduation. We find no effects of training organization on class position." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; I 2.2.2 Osteuropa; Berufsausbildung; Betriebliche Berufsausbildung; Schulische Berufsausbildung; Osteuropäischer Transformationsprozess; Ungarn